2015
DOI: 10.1542/peds.2014-2121
|View full text |Cite
|
Sign up to set email alerts
|

Core Symptoms of Autism Improved After Vitamin D Supplementation

Abstract: Autism spectrum disorder (ASD) is a common neurodevelopmental disorder caused by a complex interaction between genetic and environmental risk factors. Among the environmental factors, vitamin D 3 (cholecaliferol) seems to play a significant role in the etiology of ASD because this vitamin is important for brain development. Lower concentrations of vitamin D 3 may lead to increased brain size, altered brain shape, and enlarged ventricles, which have been observed in patients with ASD. Vitamin D 3 is converted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 21 publications
0
72
0
2
Order By: Relevance
“…Furthermore, an early report of vitamin D supplementation providing protective and restorative effects on ASD features in rat pups24 increased interest in the therapeutic potential of vitamin D for ASD. This was followed by a case study reporting improvement of core ASD symptoms following 150 000 IU/month for 2 months+400 IU/day in a 32 month-old Chinese boy with VDD and ASD 25. Subsequently, two open-label studies were published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an early report of vitamin D supplementation providing protective and restorative effects on ASD features in rat pups24 increased interest in the therapeutic potential of vitamin D for ASD. This was followed by a case study reporting improvement of core ASD symptoms following 150 000 IU/month for 2 months+400 IU/day in a 32 month-old Chinese boy with VDD and ASD 25. Subsequently, two open-label studies were published.…”
Section: Discussionmentioning
confidence: 99%
“…VDD has been implicated in the development of ASD symptoms in an animal model 24. Low-level evidence based on a single case report25 and two open-label studies support the role of vitamin D supplementation in ASD 26 27. Additionally, a single, double-blind, randomised, placebo-controlled trial reported benefit of supplementation in ASD 28.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, maternal/neonatal VD, in particular VD 3 , deficiency has been proposed as a possible environmental risk factor for ASD [105,106] due to its involvement in early brain development [107], immune system modulation [108], and gene regulation [109].…”
Section: Immunological Pathwaymentioning
confidence: 99%
“…Mostafa and Al-Ayadhi [141] reported that vitamin D deficiency could be involved in autoantibody production in patients with autism, and Cannell [146] suggested that vitamin D may reduce the severity of autism symptoms by its anti-inflammatory activity. A case report [147], along with open and controlled trials [142,148], observed an ASD symptom scores reduction after vitamin D 3 supplementation. However, recent placebo-controlled clinical trials have found divergent results following vitamin D 3 supplementation for ASD [149,150].…”
Section: Supplementsmentioning
confidence: 96%